2008
DOI: 10.1094/cchem-85-2-0196
|View full text |Cite
|
Sign up to set email alerts
|

Dry‐Milling and Fractionation of Transgenic Maize Seed Tissues with Green Fluorescent Protein as a Tissue Marker

Abstract: The efficiency of fractionating cereal grains (e.g., dry corn milling) can be evaluated and monitored by quantifying the proportions of seed tissues in each of the recovered fractions. The quantities of individual tissues are typically estimated using indirect methods such as quantifying fiber or ash to indicate pericarp and tip cap contents, and oil to indicate germ content. More direct and reliable methods are possible with tissue‐specific markers. We used two transgenic maize lines, one containing the fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Because the majority of oil accumulates in the corn germ, the oil content and recovery in each fraction were commonly used to estimate the purity of the germ and endosperm fractions. Targeted expression of green fluorescent protein (GFP) was recently used as marker 16 to study fractionation efficiency, but GFP would need to be coexpressed with the desired recombinant protein to improve on the oil method to estimate fractionation efficiency for a specific grain. The typical oil content in an industrial dry-milled germ-rich fraction for producing foodgrade corn grits and flour is about 23% db (dry basis), 17 which corresponds to about 70% purity based on the assumption that pure germ contains 33% oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the majority of oil accumulates in the corn germ, the oil content and recovery in each fraction were commonly used to estimate the purity of the germ and endosperm fractions. Targeted expression of green fluorescent protein (GFP) was recently used as marker 16 to study fractionation efficiency, but GFP would need to be coexpressed with the desired recombinant protein to improve on the oil method to estimate fractionation efficiency for a specific grain. The typical oil content in an industrial dry-milled germ-rich fraction for producing foodgrade corn grits and flour is about 23% db (dry basis), 17 which corresponds to about 70% purity based on the assumption that pure germ contains 33% oil.…”
Section: Introductionmentioning
confidence: 99%
“…60% germ yield. 16 The oil contents of the endosperm-rich fractions are typically less than 1% from an effective industrial dry-milling process.…”
Section: Introductionmentioning
confidence: 99%
“…In kernels containing r-protein expressed in germ, about 70% of the protein, can be recovered in 20-25% of the mass (9)(10)(11). The starch-rich endosperm could be directly used as a fermentation feedstock to produce biofuel and/or industrial chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…24 Although efforts have been focused on optimizing wet-milling conditions for maize fractionation, much less has been done to study the effects of wet-milling on recombinant protein recovery from transgenic maize. Fractionation studies for recovery of recombinant proteins have been carried out for germ-targeted 12,[25][26][27] and endosperm-targeted proteins 20,25,28 mainly using dry-milling or other non-wet-milling procedures.…”
Section: Introductionmentioning
confidence: 99%
“…27 Dry-milling and hand fractionation of transgenic maize expressing the green fluorescent protein under control of an embryo-or endosperm-specific promoter were used to study the efficiency of the fractionation procedures. 25 Standard dry-milling procedures were also used to study the benefit of fractionation in purification of a recombinant dog lipase targeted to be expressed in the endosperm of transgenic maize. 20 In this study, it was reported that recombinant lipase can be extracted from both endosperm and germ fractions, but utilization of endosperm fraction can eliminate the need for germ defatting and its effects on recombinant protein purification.…”
Section: Introductionmentioning
confidence: 99%